Clinical case report of patients with osteosarcoma and anticancer benefit of calycosin against human osteosarcoma cells. Issue 6 (16th January 2019) - Qiu, Rubiao; Ma, Gang; Li, Xueyu; Shi, Qunfeng; Li, Xinning; Zhou, Xiong; Tang, Yuanyuan; Xie, Zhaodi; Liao, Shijie; Qin, Yiwu; Wang, Ruyue; Ye, Yu; et al.
Abstract: Osteosarcoma (OS) is a malignant neoplasia in bone, characterized with main occurrence in teenagers. Calycosin (CC), a bioactive compound, is found to play potent pharmacological effects against cancer. Our previous study indicates CC‐exerted benefits for anti‐OS effect. However, further molecular mechanism behind this action needs to be investigated. In this study, human OS samples and clinical data were collected and used for further test and analysis. In addition, human osteosarcoma cell line (143B) and tumor‐xenograft nude mice were used to evaluate antineoplastic activities of CC through a series of biochemical methods and immunoassays, respectively. Compared with non‐OS controls, human OS samples showed increased levels of neoplastic microRNA‐223 (miR‐223), and elevated expressions of NF‐κBp65, IκBα proteins in tumor cells. In cell culture study, CC‐treated 143B cells showed reduced cell growth, increased lactic dehydrogenase (LD) content, and downregulated cellular miR‐223 level. Immunolabeled cells of proliferating cell nuclear antigen, B‐cell lymphoma 2 (Bcl‐2), poly(ADP‐ribose) polymerase (PARP) in CC treatments were decreased dose‐dependently, while caspase‐3 positive cells were elevated. Further, protein expressions of NF‐κBp65, IκBα in CC‐treated cells were downregulated. In addition, tumor‐xenograft nude mice followed by CC treatments exhibited reductions of tumor mass, miR‐223 levels, and Bcl‐2, PARP‐positive cells, as well as downregulations of NF‐κBp65, IκBα protein expressions in OS samples. Taken together, these experimental findings reveal that CC exhibits potential pharmacological activities against OS through inducing apoptosis and inhibiting miR‐223‐IκBα signaling pathway in neoplastic cells. Abstract : Our current findings suggest that calycosin benefits potential pharmacological activities against osteosarcoma, possibly linking to inducing apoptosis by regulating miR‐223‐IκBα pathway axis.